Has the cesarean epidemic in Czechia been reversed despite fertility postponement? - Tomáš Fait; Anna Šťastná; Jiřina Kocourková; Eva Waldaufová; Luděk Šídlo; Michal Kníže (BMC Pregnancy and Childbirth, 2022)
Abstract Background Although the percentage of cesarean sections (CS) in Czechia is below the average of that of other developed countries (23.6%), it still exceeds WHO recommendations (15%). The first aim of the study is to examine the association between a CS birth and the main health factors and sociodemographic characteristics involved, while the second aim is to examine recent trends in the CS rate in Czechia.  Methods Anonymized data on all mothers in Czechia for 2018 taken from the National Register of Expectant Mothers was employed. The risk of cesarean delivery for the observed factors was tested via the construction of a binary logistic regression model that allowed for adjustments for all the other covariates in the model. Results Despite all the covariates being found to be statistically significant, it was determined that health factors represented a higher risk of a CS than sociodemographic characteristics. A previous CS was found to increase the risk of its recurrence by 33 times (OR = 32.96, 95% CI 30.95–35.11, p<0.001). The breech position increased the risk of CS by 31 times (OR = 31.03, 95% CI 28.14–34.29, p<0.001). A multiple pregnancy increased the odds of CS six-fold and the use of ART 1.8-fold. Mothers who suffered from diabetes before pregnancy were found to be twice as likely to give birth via CS (OR = 2.14, 95% CI 1.76–2.60, p<0.001), while mothers with gestational diabetes had just 23% higher odds of a CS birth (OR = 1.23, 95% CI 1.16–1.31, p<0.001). Mothers who suffered from hypertension gave birth via CS twice as often as did mothers without such complications (OR = 2.01, 95% CI 1.86–2.21, p<0.001). Conclusions The increasing age of mothers, a significant risk factor for a CS, was found to be independent of other health factors. Accordingly, delayed childbearing is thought to be associated with the increase in the CS rate in Czechia. However, since other factors come into play, further research is needed to assess whether the recent slight decline in the CS rate is not merely a temporal trend.